Protein aggregation as an antibiotic design strategy. Issue 5 (9th December 2015) - Bednarska, Natalia G.; van Eldere, Johan; Gallardo, Rodrigo; Ganesan, Ashok; Ramakers, Meine; Vogel, Isabel; Baatsen, Pieter; Staes, An; Goethals, Marc; Hammarström, Per; Nilsson, K. Peter R.; Gevaert, Kris; et al.
Summary: Taking advantage of the xenobiotic nature of bacterial infections, we tested whether the cytotoxicity of protein aggregation can be targeted to bacterial pathogens without affecting their mammalian hosts. In particular, we examined if peptides encoding aggregation‐prone sequence segments of bacterial proteins can display antimicrobial activity by initiating toxic protein aggregation in bacteria, but not in mammalian cells. Unbiased in vitro screening of aggregating peptide sequences from bacterial genomes lead to the identification of several peptides that are strongly bactericidal against methicillin‐resistant S taphylococcus aureus . Upon parenteral administration in vivo, the peptides cured mice from bacterial sepsis without apparent toxic side effects as judged from histological and hematological evaluation. We found that the peptides enter and accumulate in the bacterial cytosol where they cause aggregation of bacterial polypeptides. Although the precise chain of events that leads to cell death remains to be elucidated, the ability to tap into aggregation‐prone sequences of bacterial proteomes to elicit antimicrobial activity represents a rich and unexplored chemical space to be mined in search of novel therapeutic strategies to fight infectious diseases. Abstract : Protein aggregation is often detrimental to cellular health; both through loss of native function and gain of toxic properties. We hypothesized that is would be possible to trigger aggregation within bacterial cells by exposing them to aggregation prone polypeptide fragments from their own proteome. Using this design principle we here show that it is possible to make antimicrobial peptides that display aggregation‐associated bactericidal activity which is non‐toxic to mammalian cells.